A comunicação nas organizações/marcas frente à pandemia : vertentes e reflexões - Faleiros, Bruna Mariano [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
One of the most valued assets of an organization are the brands, which relate to the organization's personality and expression. A brand is the combination of tangible and intangible characteristics, the set of benefits, attributes, values and identity that represent an organization. The pandemic of the new coronavirus brought a new reality to the work market, and organizations had to adapt to this new dynamic. This study presents some communicational actions in this period, of five brands present in Brazil, describing some behaviors and aspects in social media, from an observational netnographic research of the profiles of these brands on Facebook and Instagram. The results contribute to a reflection on the importance of collaborative and/or socially oriented communication strategies in a moment of instability, volatility, uncertainty, complexity and ambiguity of the scenario, besides serving as a metric to subsidize organizations in this complex task of adapting to the digital culture.

Um dos bens mais valorizados das organizações são suas marcas, que dizem respeito a personalidade e expressão delas. Uma marca é a junção de características tangíveis e intangíveis, o conjunto de benefícios, atributos, valores e identidade que representam uma organização. A pandemia do novo coronavírus trouxe uma nova realidade para o mercado de trabalho e as organizações tiveram que se adaptar a essa nova dinâmica. Este estudo apresenta algumas ações comunicacionais neste período, de cinco marcas presentes no Brasil, descrevendo alguns comportamentos e aspectos nas mídias sociais, a partir de uma pesquisa netnográfica observacional dos perfis dessas marcas no Facebook e no Instagram. Os resultados contribuem para uma reflexão sobre a importância das estratégias de comunicação colaborativas e/ou voltadas ao social num momento de instabilidade, volatilidade, incerteza, complexidade e ambiguidade do cenário, além de servir como métrica para subsidiar as organizações nesta empreitada complexa de adaptação à cultura digital.
Communication in organizations/brands facing the pandemic : aspects and reflections
Keywords: Brand; Branding (Marketing); Companies; Communication; Public relations; Pandemic; Marca de produtos; Empresas; Comunicação; Relações públicas; Pandemia